2015
DOI: 10.5152/akd.2014.5787
|View full text |Cite
|
Sign up to set email alerts
|

Is the neutrophil-to-lymphocyte ratio indicative of inflammatory state in patients with obesity and metabolic syndrome?

Abstract: Objective:Obesity causes subclinical inflammation. Leukocyte count and high-sensitivity C-reactive protein (hs-CRP) are used to indicate inflammation in clinical practice. Also, inflammatory markers are evaluated as important indicators of cardiovascular risk in patients with obesity and metabolic syndrome (MetS). We aimed to investigate the usage of the neutrophil-lymphocyte ratio (NLR) as an inflammatory marker in obese patients with and without MetS.Methods:The study included a total of 1267 patients. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 36 publications
2
50
2
4
Order By: Relevance
“…But it was not statistically significant (25). Additionally, in that study, it was reported that NLR , itself, could not be a reliable marker of inflammation, and did not differ according to the degree of obesity (25). Similar to that study, we found that there was no difference between the initial NLR value and the value after weight loss and NLR was not affected by BMI.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…But it was not statistically significant (25). Additionally, in that study, it was reported that NLR , itself, could not be a reliable marker of inflammation, and did not differ according to the degree of obesity (25). Similar to that study, we found that there was no difference between the initial NLR value and the value after weight loss and NLR was not affected by BMI.…”
Section: Discussionsupporting
confidence: 77%
“…But it was not statistically significant (25). Additionally, in that study, it was reported that NLR , itself, could not be a reliable marker of inflammation, and did not differ according to the degree of obesity (25).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, NLR is calculated from a convenient and inexpensive test that is a useful predictor of LN metastasis, and hopefully could be used for the management and treatment of endometrial cancers. NLR was not affected by obesity, so it would be beneficial for patients with endometrial cancers [23]. However, as it is a systemic inflammatory marker, consideration should be given to the effects of other general conditions (e.g., smoking and common inflammatory disease) [24].…”
Section: Discussionmentioning
confidence: 99%
“…We interrogated the NTR/NESDA twins to identify associations between physical activity genes and white blood cell count, an indicator of inflammation. In addition to age and sex, we adjusted the models for BMI and smoking status to measure the association of physical activity with white blood cell count independent of BMI and smoking status [61][62][63][64] . We also adjusted the model for the random effects for family and monozygosity resulting in:…”
Section: Phenotype Cohortsmentioning
confidence: 99%